Parent-of-Origin Effects on Glucose Homeostasis in Polycystic Ovary Syndrome - Kobaly, Kristen (Endocrine Society, 2014)
CONTEXT: Polycystic ovary syndrome (PCOS) is a highly heritable complex trait. Parents of affected women have reproductive and metabolic phenotypes. OBJECTIVE: We tested the hypothesis that there are parental effects on the heritability of fasting dysglycemia in women with PCOS. DESIGN AND SETTING: This was a cross-sectional study at an academic medical center. PARTICIPANTS: Participants included 367 women with PCOS and their parents (1101 total subjects). MAIN OUTCOME MEASURES: We compared maternal and paternal contributions to heritability of fasting dysglycemia and to transmission of the PCOS susceptibility allele of D19S884 within the fibrillin-3 gene (D19S884-A8) on fasting dysglycemia. RESULTS: Fathers had higher fasting glucose levels, prevalence of fasting dysglycemia and proinsulin to insulin molar ratios (P < .0001), a marker of defective insulin processing, compared with mothers. Heritability of fasting dysglycemia was significant in PCOS families (h(2) = 37%, SE = 10%, P = .001). Maternal heritability (h(2) = 51%, SE = 15%, P = .0009) was higher than paternal heritability (h(2) = 23 %, SE = 23%, P = .186) of fasting dysglycemia after adjustment for age and body mass index. Within dysglycemic probands, there was increased maternal compared with paternal transmission of D19S884-A8 (maternal 84% vs paternal 45%, χ(2) = 6.51, P = .011). CONCLUSIONS: There was a sex difference in the parental metabolic phenotype with fathers having an increased risk of fasting dysglycemia and evidence for pancreatic β-cell dysfunction compared with mothers. However, only maternal heritability had significant effects on the prevalence of fasting dysglycemia in women with PCOS. Furthermore, there were maternal parent-of-origin effects on transmission of D19S884-A8 probands with fasting dysglycemia. These findings suggest that maternal factors, genetic and perhaps epigenetic, contribute to the metabolic phenotype in affected women.